2018
DOI: 10.3389/fimmu.2018.02716
|View full text |Cite
|
Sign up to set email alerts
|

Structural Immunology of Complement Receptors 3 and 4

Abstract: Complement receptors (CR) 3 and 4 belong to the family of beta-2 (CD18) integrins. CR3 and CR4 are often co-expressed in the myeloid subsets of leukocytes, but they are also found in NK cells and activated T and B lymphocytes. The heterodimeric ectodomain undergoes considerable conformational change in order to switch the receptor from a structurally bent, ligand-binding in-active state into an extended, ligand-binding active state. CR3 binds the C3d fragment of C3 in a way permitting CR2 also to bind concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 179 publications
(272 reference statements)
6
104
0
1
Order By: Relevance
“…36 CR3 and CR4 were proved to enable complement-dependent cell cytotoxicity toward antibody-coated tumor cells as part of biological therapy. 37 As revealed in our sub-network, KEGG pathways were also predicted correlations with the hematopoietic cell lineage and immunodeficiency, providing a clue that ITGAM, ITGB2 and ITGAX might also be involved in AL amyloidosis progression via regulating immune response. Furthermore, the study found candidate small molecules that may be involved in promoting or suppressing the development of AL amyloidosis.…”
Section: Discussionsupporting
confidence: 61%
“…36 CR3 and CR4 were proved to enable complement-dependent cell cytotoxicity toward antibody-coated tumor cells as part of biological therapy. 37 As revealed in our sub-network, KEGG pathways were also predicted correlations with the hematopoietic cell lineage and immunodeficiency, providing a clue that ITGAM, ITGB2 and ITGAX might also be involved in AL amyloidosis progression via regulating immune response. Furthermore, the study found candidate small molecules that may be involved in promoting or suppressing the development of AL amyloidosis.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, MAC-1 binds several matrix proteins, like collagen, fibronectin, fibrinogen, vitronectin, Cyr61, and plasminogen. Further, MAC-1 is the primary receptor for complement C3-opsonized pathogens and immune complexes at high affinity, recognizing iC3b, C3dg, and C3d, and mediates their internalization [56,57]. Due to this property, MAC-1 has also been termed complement receptor 3 (CR3).…”
Section: Ligands Of β2 Integrinsmentioning
confidence: 99%
“…The heterodimer CD11b/CD18 is called complement receptor 3 (CR3, Mac1 or α M β 2 ). CR3 is a multi-functional receptor which was described as predominantly expressed on myeloid and NK cells (Ross and Vetvicka, 1993;Vorup-Jensen and Jensen, 2018) and involved in NK cell cytotoxicity (Lee et al, 2017). CR3 can interact with Fc receptors for adhesion to immune complexes and therefore enhance cell mediated antibody-dependent cytotoxicity (Ortiz-Stern and Rosales, 2003).…”
Section: Discussionmentioning
confidence: 99%